Alumina ceramic granulation powder and preparation method thereof

Through technical means such as vacuum hot pressing and ultrasonic treatment, combined with ball milling and spray granulation of various raw materials, the purity and particle size distribution of alumina ceramic granulation powder is solved, the sintering performance and porcelain density are improved, and the ceramics are improved. Mechanical properties and compactness.

CN119219399AActive Publication Date: 2024-12-31YONGZHOU MINGRUI CERAMIC TECH CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411730004.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2024-12-31
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

The alumina powder of alumina ceramic granulated powder has low purity, wide particle size distribution, poor sintering performance, resulting in a decrease in the mechanical properties of the ceramic, poor density of porcelain-formed parts and large shrinkage.

Method used

By mixing alumina powder with alumina whiskers for vacuum hot pressing, ball milling and ultrasonic treatment of raw materials such as polyethylene glycol-cellulose nanocrystals, gneissite powder, magnesium feldspar powder, ore powder-carbide steel slag and other raw materials, ball milling and ultrasonic treatment. , a high-pressure, heat-treated slurry was formed, and finally spray granulated to obtain alumina ceramic granulation powder.

Benefits of technology

The alumina content, narrow particle size distribution, spherical shape and fluidity of alumina ceramic granulated powder are improved, the sintering performance is improved, the density and mechanical properties of porcelain are improved, and the structural stability and performance of ceramics are ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention provides aluminum oxide ceramic granulation powder and a preparation method thereof.The preparation method comprises the steps that S1, aluminum oxide powder and aluminum oxide whiskers are mixed and subjected to vacuum hot pressing, and pretreated aluminum oxide is obtained; s2, the pretreated aluminum oxide, polyethylene glycol-cellulose nanocrystals, gneiss powder, akermanite powder, mineral powder-carbonized steel slag, a dispersing agent and a plasticizer are subjected to ball milling to obtain powder, the powder is added into water, ultrasonic treatment is conducted, plasma treatment is conducted after ultrasonic treatment is completed, and slurry is obtained; s3, performing high-pressure and heating treatment on the slurry, then releasing the pressure to normal pressure, and continuing ultrasonic treatment during the period to obtain a mixture; s4, the mixture is subjected to spray granulation, sieving, iron removal and homogenization for standby application, and the aluminum oxide ceramic granulation powder is obtained. The aluminum oxide content of the aluminum oxide ceramic granulation powder is 99% or above, the particle size is small, the particle size distribution is narrow, the sphericity degree and the fluidity are good, the sintering performance is good, the ceramic forming density is high, the compactness is high, and the obtained aluminum oxide ceramic is high in mechanical property and wide in application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of alumina ceramics, and in particular to alumina ceramic granulated powder and a preparation method thereof. Background Art

[0002] Alumina ceramics are an advanced ceramic material with aluminum oxide (Al2O3) as the main component. They have a series of excellent properties such as high mechanical strength, high volume resistivity, good electrical insulation, high strength, wear resistance and oxidation resistance. They are mainly used in high-end ceramic fields such as functional ceramics and structural ceramics.

[0003] Alumina ceramic materials are mainly made of α-alumina powder as raw material and prepared by sintering. α-alumina powder is generally prepared by stirring granulation, pressure granulation, spray granulation or freeze drying. Among them, spray drying has fast drying speed and good powder dispersibility, and is currently the most widely used. Alumina has extremely strong ionic bonding, and its melting point reaches 2050℃, requiring a higher sintering temperature. However, due to the poor fluidity of the slurry, the subsequent granulation powder performance is affected, and the particle strength is poor. The alumina powder of the prepared alumina ceramic granulation powder has low purity and wide particle size distribution, resulting in poor sintering performance of the powder. The sintering temperature reaches above 1550℃. The excessively high sintering temperature makes the main crystal phase of the ceramic grow larger, and the residual pores gather and grow, resulting in reduced mechanical properties of the material, poor density of the finished ceramic parts, and large shrinkage. Summary of the invention

[0004] In view of this, the present invention proposes an alumina ceramic granulated powder and a preparation method thereof to solve the above technical problems.

[0005] The technical solution of the present invention is achieved in this way: A method for preparing alumina ceramic granulated powder, the specific steps comprising: S1, mixing alumina powder and alumina whiskers, and vacuum hot pressing to obtain pretreated alumina; The vacuum hot pressing has a vacuum degree of 8-12 kPa, a heating rate of 10-20° C. / min, a temperature of 600-700° C., and a time of 10-20 min; S2, ball-milling the pretreated alumina, polyethylene glycol-cellulose nanocrystals, gneiss rock powder, magnesia feldspar powder, mineral powder-carbonized steel slag, dispersant and plasticizer to obtain a powder, adding the powder to water, ultrasonically treating it, and plasma treating it after the ultrasonic treatment to obtain a slurry; The plasma treatment is carried out at 300-350W in a nitrogen atmosphere for 3-6 minutes with a nitrogen pressure of 0.1-0.3MPa; S3, subjecting the slurry to high pressure and heating treatment, and then releasing the pressure to normal pressure, during which ultrasonic treatment is continued to be performed, to obtain a mixture; The high pressure and heating treatment is to increase the pressure to 20-40MPa and the temperature to 100-150°C for 20-30min; the pressure relief rate is 1-3MPa / min; the power of the ultrasonic treatment is 80-120W; S4, spray granulating the mixture, sieving, removing iron, homogenizing and setting aside to obtain alumina ceramic granulated powder.

[0006] Furthermore, in step S1, the aluminum oxide content of the aluminum oxide powder is greater than 99.99%, and the original crystal size is 0.6-0.7 μm; the aluminum oxide whiskers are fibrous α-aluminum oxide whiskers with a diameter of 0.55-0.85 μm and a length of 10-12 μm; the mass ratio of the aluminum oxide powder to the aluminum oxide whiskers is (100-120): (3-5).

[0007] Furthermore, in step S2, the mass ratio of the polyethylene glycol-cellulose nanocrystals, gneiss rock powder, magnesia feldspar powder, mineral powder-carbonized steel slag, dispersant, plasticizer and alumina powder is (1-2): (0.2-0.4): (0.1-0.3): (0.1-0.2): (0.5-3): (0.5-1.5): (100-120); the ball milling medium is a polyurethane grinding ball, the rotation speed is 400-600rpm, the time is 18-24h, and the material-ball ratio is 1:2-3; the material-liquid ratio of the powder to water is 1:30-50g / mL; and the ultrasonic treatment is carried out at 20-30kHz and 100-200W for 30-60min.

[0008] Furthermore, in step S2, the polyethylene glycol-cellulose nanocrystals are prepared by adding cellulose nanocrystals to N,N-dimethylformamide at a solid-liquid ratio of 1:20-30 g / mL, ultrasonically dispersing the cellulose nanocrystals at 20-30 kHz and 40-60° C., adding polyethylene glycol to the dispersion at a mass ratio of cellulose nanocrystals to polyethylene glycol of 1:0.2-0.4, continuously stirring at 110-140° C. for 24-48 hours, washing and drying to obtain polyethylene glycol-cellulose nanocrystals.

[0009] Cellulose nanocrystals are rod-shaped nanomaterials extracted from cellulose. They are usually separated from fibers by sulfuric acid or hydrochloric acid. During acid treatment, the disordered and semi-crystalline parts of cellulose are preferentially hydrolyzed, while the crystalline parts are better able to resist acid hydrolysis and are thus completely retained, thus obtaining cellulose nanocrystals. Cellulose nanocrystals have excellent properties such as complete biodegradability, low density, and high strength.

[0010] Polyethylene glycol has good compatibility with many organic components and has excellent lubricity, moisturizing, dispersibility, adhesiveness, antistatic agent and softener. It is widely used in cosmetics, pharmaceuticals, chemical fiber, rubber, plastics, papermaking, paint, electroplating, pesticides, metal processing and food processing industries.

[0011] Furthermore, in step S2, the gneiss rock powder is siliceous gneiss rock powder with a fineness of less than 15%; and the dispersant is a polymer dispersant AKM-0531.

[0012] Gneiss stone powder is a stone powder produced in the process of producing machine-made sand using gneiss. The content is preferably 65%-75%. Reasonable and effective use of the gneiss stone powder waste produced in the process of machine-made sand production can improve the performance of ceramics to a certain extent.

[0013] Furthermore, in step S2, the mineral powder-carbonized steel slag is prepared by stirring the steel slag slurry, continuously introducing CO2, filtering and drying to form carbonized steel slag powder, and uniformly mixing the carbonized steel slag powder and the mineral powder in a mass ratio of 1:4-5 to obtain the mineral powder-carbonized steel slag; The stirring speed is 300-400 rpm, the temperature is 55-60°C; the CO2 flow rate is 2.2-2.4 L / min, the time is 2-4h; the drying temperature is 100-110°C.

[0014] Steel slag contains abundant alkaline calcium oxides, which can react with carbon dioxide to form stable solid calcium carbonate. Therefore, carbonization technology can be used to treat steel slag. Carbonization treatment can not only fix carbon dioxide to produce environmental benefits, but also consume unstable components in steel slag (such as free calcium oxide and free magnesium oxide), and grow a dense shell composed of nano-scale calcium carbonate grains on the surface of steel slag. The calcium carbonate content is greater than 20%, and the calcium carbonate is well crystallized. The active aluminum in the mineral powder can react with the calcium carbonate on the surface of the steel slag to form calcium aluminate, which can be used as a solvent in the ceramic sintering process to reduce the sintering temperature, promote bonding, and improve density. It has a positive effect on the various properties of ceramics. Therefore, carbonization also gives steel slag new reactivity, making carbonized steel slag have higher application value in the field of ceramics.

[0015] Furthermore, in step S4, the inlet temperature of the spray granulation is 185-195°C, the outlet temperature is 90-100°C, and the atomizer speed is 15-25Hz; the sieving is through 60-mesh and 200-mesh sieves, and the powder between the two layers of sieves is taken.

[0016] Alumina ceramic granulated powder is prepared by the above preparation method.

[0017] Compared with the prior art, the present invention has the following beneficial effects: 1. The alumina ceramic granulated powder obtained by the preparation method of the present invention has an alumina content of more than 99%, a small particle size, a narrow particle size distribution, good sphericity and fluidity, good sintering performance, high ceramic density, high compactness, and the obtained alumina ceramic has high mechanical properties.

[0018] 2. The present invention mixes alumina whiskers and alumina powder and performs vacuum hot pressing treatment, which can improve the mechanical properties of ceramics, improve bending strength and thermal shock resistance; after ball milling of each raw material, the combination of ultrasonic treatment and plasma treatment not only improves the uniformity, but also improves the fluidity and adhesion of the slurry, enhances surface activity, and is beneficial to subsequent improvement of sintering performance and promotion of molding; the slurry is subjected to high pressure and heat treatment to rapidly heat up, improve the ceramic density, and improve the sintering performance. Reducing the pressure to normal pressure can effectively reduce the internal stress of the material, avoid excessive temperature difference that causes the main crystal phase of the ceramic to be too large or uneven in shape, and ensure the subsequent structural stability and performance stability of the ceramic. DETAILED DESCRIPTION

[0019] In order to better understand the technical content of the present invention, specific embodiments are provided below to further illustrate the present invention.

[0020] Unless otherwise specified, the experimental methods used in the embodiments of the present invention are all conventional methods.

[0021] Unless otherwise specified, the materials, reagents, etc. used in the embodiments of the present invention can be obtained from commercial sources.

[0022] The mineral powder of the present invention is S95 or above, and has a particle size of 5-25 μm.

[0023] The gneiss rock powder of the present invention is purchased from Shaanxi Redeboer Investment Co., Ltd.

[0024] The dispersant of the present invention is a polymer dispersant AKM-0531, which was purchased from Shanghai Jiangze New Materials Co., Ltd.

[0025] The aluminum oxide content of the aluminum oxide powder in the present invention is greater than 99.99%, and the original crystal size is 0.6-0.7 μm.

[0026] The alumina whiskers in the present invention are fibrous α-alumina whiskers with a diameter of 0.55-0.85 μm and a length of 10-12 μm.

[0027] The gneiss powder in the present invention is siliceous gneiss powder with a fineness of less than 15%.

[0028] Example 1 The alumina ceramic granulation powder of this embodiment includes the following raw materials in parts by weight: 110 parts of alumina powder, 4 parts of alumina whiskers, 1.5 parts of polyethylene glycol-cellulose nanocrystals, 0.34 parts of gneiss rock powder, 0.2 parts of magnesia feldspar powder, 0.15 parts of mineral powder-carbonized steel slag, 2 parts of dispersant, and 1 part of plasticizer.

[0029] Polyethylene glycol-cellulose nanocrystals: Add cellulose nanocrystals to N,N-dimethylformamide at a solid-liquid ratio of 1:25 g / mL, and ultrasonically disperse them at 25 kHz and 50°C. Add polyethylene glycol to the dispersion at a mass ratio of cellulose nanocrystals to polyethylene glycol of 1:0.3. Stir continuously at 125°C for 36 hours, wash and dry to obtain polyethylene glycol-cellulose nanocrystals.

[0030] Mineral powder-carbonized steel slag: The steel slag slurry was stirred at 350 rpm and 58 °C for 3 h, and 2.3 L / min of CO2 was continuously introduced. The mixture was filtered and dried at 105 °C to form carbonized steel slag powder. The carbonized steel slag powder and mineral powder were evenly mixed in a mass ratio of 1:4.5 to obtain mineral powder-carbonized steel slag.

[0031] The preparation method of the above-mentioned alumina ceramic granulated powder comprises the following specific steps: S1, mixing alumina powder and alumina whiskers, and performing vacuum hot pressing for 15 min at a vacuum degree of 10 kPa, a heating rate of 15°C / min, and a temperature of 650°C to obtain pretreated alumina; S2, pretreated alumina, polyethylene glycol-cellulose nanocrystals, gneiss rock powder, magnesia feldspar powder, mineral powder-carbonized steel slag, dispersant and plasticizer were mixed, and ball milled for 20 hours with polyurethane grinding balls, with a material-ball ratio of 1:2.5 and a rotation speed of 500 rpm to obtain powder, and the powder was added into water according to a material-liquid ratio of 1:40 g / mL, and ultrasonically treated for 45 minutes at 25kHz and 150W, and plasma treated for 5 minutes after the ultrasonic treatment, and the specific conditions were: 320W, nitrogen atmosphere, nitrogen pressure 0.2MPa, to obtain slurry; S3, increasing the pressure to 30 MPa and the temperature to 130° C., subjecting the slurry to high pressure and heating treatment for 25 min, and then releasing the pressure to normal pressure at a pressure release rate of 2 MPa / min, during which time ultrasonic treatment at 100 W is continued to obtain a mixture; S4. The mixture is spray granulated with an inlet temperature of 190°C, an outlet temperature of 95°C, and an atomizer speed of 20Hz. After granulation, it is sieved through a 60-mesh and a 200-mesh sieve. The powder between the two layers of sieves is taken, iron is removed, and homogenized for 2 hours for standby use to obtain alumina ceramic granulated powder.

[0032] Example 2 The alumina ceramic granulation powder of this embodiment includes the following raw materials in parts by weight: 100 parts of alumina powder, 3 parts of alumina whiskers, 1 part of polyethylene glycol-cellulose nanocrystals, 0.2 parts of gneiss rock powder, 0.1 parts of magnesia feldspar powder, 0.1 parts of mineral powder-carbonized steel slag, 0.5 parts of dispersant, and 0.5 parts of plasticizer.

[0033] Polyethylene glycol-cellulose nanocrystals: Add cellulose nanocrystals to N,N-dimethylformamide at a solid-liquid ratio of 1:20 g / mL, and ultrasonically disperse them at 20 kHz and 40°C. Add polyethylene glycol to the dispersion at a mass ratio of cellulose nanocrystals to polyethylene glycol of 1:0.2. Stir continuously at 110°C for 24 hours, wash and dry to obtain polyethylene glycol-cellulose nanocrystals.

[0034] Mineral powder-carbonized steel slag: The steel slag slurry was stirred at 300 rpm and 550 °C for 2 h, and 2.2 L / min of CO2 was continuously introduced. The mixture was filtered and dried at 100 °C to form carbonized steel slag powder. The carbonized steel slag powder and mineral powder were evenly mixed in a mass ratio of 1:4 to obtain mineral powder-carbonized steel slag.

[0035] The preparation method of the above-mentioned alumina ceramic granulated powder comprises the following specific steps: S1, mixing alumina powder and alumina whiskers, and performing vacuum hot pressing for 10 min at a vacuum degree of 8 kPa, a heating rate of 10 ° C / min, and a temperature of 600 ° C to obtain pretreated alumina; S2, pretreated alumina, polyethylene glycol-cellulose nanocrystals, gneiss rock powder, magnesia feldspar powder, mineral powder-carbonized steel slag, dispersant and plasticizer were mixed, and ball milled for 18 hours with polyurethane grinding balls, with a material-ball ratio of 1:2 and a rotation speed of 400 rpm to obtain powder, and the powder was added into water according to a material-liquid ratio of 1:30 g / mL, and ultrasonically treated for 30 minutes at 20 kHz and 100 W, and plasma treated for 3 minutes after the ultrasonic treatment, and the specific conditions were: 300 W, nitrogen atmosphere, nitrogen pressure 0.1 MPa, to obtain slurry; S3, raising the pressure to 20 MPa and the temperature to 100° C., subjecting the slurry to high pressure and heating treatment for 20 min, and then releasing the pressure to normal pressure at a pressure release rate of 1 MPa / min, during which time ultrasonic treatment at 80 W is continued to obtain a mixture; S4. The mixture is spray granulated with an inlet temperature of 185°C, an outlet temperature of 90°C, and an atomizer speed of 15Hz. After granulation, it is sieved through a 60-mesh and a 200-mesh sieve. The powder between the two layers of sieves is taken, iron is removed, and homogenized for 2 hours for standby use to obtain alumina ceramic granulated powder.

[0036] Example 3 The alumina ceramic granulation powder of this embodiment includes the following raw materials in parts by weight: 120 parts of alumina powder, 5 parts of alumina whiskers, 2 parts of polyethylene glycol-cellulose nanocrystals, 0.4 parts of gneiss rock powder, 0.3 parts of magnesia feldspar powder, 0.2 parts of mineral powder-carbonized steel slag, 3 parts of dispersant, and 1.5 parts of plasticizer.

[0037] Polyethylene glycol-cellulose nanocrystals: Add cellulose nanocrystals to N,N-dimethylformamide at a solid-liquid ratio of 1:30 g / mL, and ultrasonically disperse them at 30 kHz and 60°C. Add polyethylene glycol to the dispersion at a mass ratio of cellulose nanocrystals to polyethylene glycol of 1:0.4. Stir continuously at 140°C for 48 hours, wash and dry to obtain polyethylene glycol-cellulose nanocrystals.

[0038] Mineral powder-carbonized steel slag: The steel slag slurry was stirred at 400 rpm and 60 °C for 4 h, and 2.4 L / min of CO2 was continuously introduced. The mixture was filtered and dried at 110 °C to form carbonized steel slag powder. The carbonized steel slag powder and mineral powder were evenly mixed in a mass ratio of 1:5 to obtain mineral powder-carbonized steel slag.

[0039] The preparation method of the above-mentioned alumina ceramic granulated powder comprises the following specific steps: S1, mixing alumina powder and alumina whiskers, and performing vacuum hot pressing for 20 min at a vacuum degree of 12 kPa, a heating rate of 20°C / min, and a temperature of 700°C to obtain pretreated alumina; S2, pretreated alumina, polyethylene glycol-cellulose nanocrystals, gneiss rock powder, magnesia feldspar powder, mineral powder-carbonized steel slag, dispersant and plasticizer were mixed, and ball milled for 24 hours with polyurethane grinding balls, with a material-ball ratio of 1:3 and a rotation speed of 600 rpm to obtain powder, and the powder was added into water according to a material-liquid ratio of 1:50 g / mL, and ultrasonically treated for 60 minutes at 30 kHz and 200 W, and plasma treated for 6 minutes after the ultrasonic treatment, and the specific conditions were: 350 W, nitrogen atmosphere, nitrogen pressure 0.3 MPa, to obtain slurry; S3, raising the pressure to 40 MPa and the temperature to 150° C., subjecting the slurry to high pressure and heating treatment for 30 min, and then releasing the pressure to normal pressure at a pressure release rate of 3 MPa / min, during which ultrasonic treatment at 120 W is continued to obtain a mixture; S4. The mixture is spray granulated with an inlet temperature of 195°C, an outlet temperature of 100°C, and an atomizer speed of 25Hz. After granulation, it is sieved through a 60-mesh and a 200-mesh sieve. The powder between the two layers of sieves is taken, iron is removed, and homogenized for 2 hours for standby use to obtain alumina ceramic granulated powder.

[0040] Test Example 1 The alumina ceramic granulated powder prepared in Examples 1-3 was subjected to a particle size distribution test and a fluidity test, wherein the fluidity test was conducted by testing the angle of repose of the alumina ceramic granulated powder.

[0041] The loss on ignition refers to the amount of mass reduction of the alumina ceramic granulated powder after calcining at 1100° C. for 2 hours, and the reduced mass is mainly the mass of the additives and water in the granulated powder.

[0042] The results are shown in Table 1.

[0043] Table 1 It can be seen from Table 1 that the alumina ceramic granulated powder prepared in Examples 1-3 of the present invention has a small particle size, a narrow particle size distribution, good fluidity and a low loss on ignition.

[0044] Comparative Example 1 The difference from Example 1 is that: the aluminum oxide whisker is missing, and the rest is the same as Example 1.

[0045] Comparative Example 2 The difference from Example 1 is that polyethylene glycol-cellulose nanocrystals are replaced by cellulose nanocrystals, and the rest is the same as Example 1.

[0046] Comparative Example 3 The difference from Example 1 is that gneiss rock powder is missing, and the rest is the same as Example 1.

[0047] Comparative Example 4 The difference from Example 1 is that magnesia chalcedony powder is missing, and the rest is the same as Example 1.

[0048] Comparative Example 5 The difference from Example 1 is that the mineral powder-carbonized steel slag is missing, and the rest is the same as Example 1.

[0049] Comparative Example 6 The difference from Example 1 is that there is no plasma treatment, and the rest is the same as Example 1.

[0050] That is, step S2 in the preparation method of alumina ceramic granulated powder of this comparative example is specifically as follows: S2. Pretreated alumina, polyethylene glycol-cellulose nanocrystals, gneiss rock powder, magnesia feldspar powder, mineral powder-carbonized steel slag, dispersant and plasticizer are mixed, and ball milled for 20 hours using polyurethane grinding balls with a material-ball ratio of 1:2.5 and a rotation speed of 500 rpm to obtain powder. The powder is added into water at a material-liquid ratio of 1:40 g / mL, and ultrasonically treated at 25 kHz and 150 W for 45 minutes to obtain a slurry.

[0051] Comparative Example 7 The difference from Example 1 is that step S3 is missing, and the rest is consistent with Example 1.

[0052] That is, the preparation method of the alumina ceramic granulated powder of this comparative example comprises the following specific steps: S1, mixing alumina powder and alumina whiskers, and performing vacuum hot pressing for 15 min at a vacuum degree of 10 kPa, a heating rate of 15°C / min, and a temperature of 650°C to obtain pretreated alumina; S2, pretreated alumina, polyethylene glycol-cellulose nanocrystals, gneiss rock powder, magnesia feldspar powder, mineral powder-carbonized steel slag, dispersant and plasticizer were mixed, and ball milled for 20 hours with polyurethane grinding balls, with a material-ball ratio of 1:2.5 and a rotation speed of 500 rpm to obtain powder, and the powder was added into water according to a material-liquid ratio of 1:40 g / mL, and ultrasonically treated for 45 minutes at 25kHz and 150W, and plasma treated for 5 minutes after the ultrasonic treatment, and the specific conditions were: 320W, nitrogen atmosphere, nitrogen pressure 0.2MPa, to obtain slurry; S3. The slurry is sprayed and granulated, with an inlet temperature of 190°C, an outlet temperature of 95°C, and an atomizer speed of 20Hz. After granulation, it is sieved through 60-mesh and 200-mesh sieves, and the powder between the two layers of sieves is taken, iron is removed, and homogenized for 2 hours for standby use to obtain alumina ceramic granulation powder.

[0053] Test Example 2 The alumina ceramic granulated powders prepared in Examples 1-3 and Comparative Examples 1-7 were subjected to sintering performance tests, and the bulk density, density of the formed green body at 100 MPa and shrinkage rate were recorded. The results are shown in Table 2.

[0054] Table 2 It can be seen from Table 2 that, compared with Comparative Examples 1-7, the alumina ceramic granulated powders of Examples 1-3 of the present invention have good sintering performance, high ceramic density, high compactness, and low shrinkage.

[0055] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing alumina ceramic granulated powder, characterized in that: The specific steps include: S1, mixing alumina powder and alumina whiskers, and vacuum hot pressing to obtain pretreated alumina; The vacuum hot pressing has a vacuum degree of 8-12 kPa, a heating rate of 10-20° C. / min, a temperature of 600-700° C., and a time of 10-20 min; S2, ball-milling the pretreated alumina, polyethylene glycol-cellulose nanocrystals, gneiss rock powder, magnesia feldspar powder, mineral powder-carbonized steel slag, dispersant and plasticizer to obtain a powder, adding the powder to water, ultrasonically treating it, and plasma treating it after the ultrasonic treatment to obtain a slurry; The plasma treatment is carried out at 300-350W in a nitrogen atmosphere for 3-6 minutes with a nitrogen pressure of 0.1-0.3MPa; S3, subjecting the slurry to high pressure and heating treatment, and then releasing the pressure to normal pressure, during which ultrasonic treatment is continued to be performed, to obtain a mixture; The high pressure and heating treatment is to increase the pressure to 20-40MPa and the temperature to 100-150°C for 20-30min; the pressure relief rate is 1-3MPa / min; the power of the ultrasonic treatment is 80-120W; S4, spray granulating the mixture, sieving, removing iron, homogenizing and setting aside to obtain alumina ceramic granulated powder.

2. The method for preparing alumina ceramic granulated powder according to claim 1, characterized in that: In step S1, the aluminum oxide content of the aluminum oxide powder is greater than 99.99%, and the original crystal size is 0.6-0.7 μm; the aluminum oxide whisker is a fibrous α-aluminum oxide whisker with a diameter of 0.55-0.85 μm and a length of 10-12 μm; the mass ratio of the aluminum oxide powder to the aluminum oxide whisker is (100-120): (3-5).

3. The method for preparing alumina ceramic granulated powder according to claim 1, characterized in that: In step S2, the mass ratio of the polyethylene glycol-cellulose nanocrystals, gneiss rock powder, magnesia feldspar powder, mineral powder-carbonized steel slag, dispersant, plasticizer and alumina powder is (1-2): (0.2-0.4): (0.1-0.3): (0.1-0.2): (0.5-3): (0.5-1.5): (100-120); the ball milling medium is a polyurethane grinding ball, the rotation speed is 400-600rpm, the time is 18-24h, and the material-ball ratio is 1:2-3; the material-liquid ratio of the powder to water is 1:30-50g / mL; and the ultrasonic treatment is carried out at 20-30kHz and 100-200W for 30-60min.

4. The method for preparing alumina ceramic granulated powder according to claim 1, characterized in that: In step S2, the polyethylene glycol-cellulose nanocrystals are prepared by adding cellulose nanocrystals to N,N-dimethylformamide at a solid-liquid ratio of 1:20-30 g / mL, ultrasonically dispersing the mixture at 20-30 kHz and 40-60° C., adding polyethylene glycol to the dispersion at a mass ratio of cellulose nanocrystals to polyethylene glycol of 1:0.2-0.4, stirring the mixture at 110-140° C. for 24-48 hours, washing and drying the mixture to obtain polyethylene glycol-cellulose nanocrystals.

5. The method for preparing alumina ceramic granulated powder according to claim 1, characterized in that: In step S2, the gneiss rock powder is siliceous gneiss rock powder with a fineness of less than 15%; and the dispersant is a polymer dispersant AKM-0531.

6. The method for preparing alumina ceramic granulated powder according to claim 1, characterized in that: In step S2, the mineral powder-carbonized steel slag is prepared by stirring the steel slag slurry, continuously introducing CO2, filtering and drying to form carbonized steel slag powder, and uniformly mixing the carbonized steel slag powder and the mineral powder in a mass ratio of 1:4-5 to obtain the mineral powder-carbonized steel slag; The stirring speed is 300-400 rpm, the temperature is 55-60°C; the CO2 flow rate is 2.2-2.4 L / min, the time is 2-4h; the drying temperature is 100-110°C.

7. The method for preparing alumina ceramic granulated powder according to claim 1, characterized in that: In step S4, the inlet temperature of the spray granulation is 185-195°C, the outlet temperature is 90-100°C, and the atomizer speed is 15-25Hz; the screening is through 60-mesh and 200-mesh sieves, and the powder between the two layers of sieves is taken.

8. Alumina ceramic granulated powder, prepared by the preparation method according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Composite mineral admixture based on gneiss powder

    CN107298538A

  • Cellulose nanocrystalline modified ceramic casting green body, and preparation method thereof

    CN108314430A

  • Electrostatic spinning nanofiber toughened aluminum oxide ceramic and preparation method thereof

    CN113816729A

  • Alumina ceramic as well as preparation method and application thereof

    CN118047594A

  • Preparation method and application of mineral powder-carbonized steel slag composite mineral admixture

    CN118084363A